Financing “a sustainable food future”: Some thoughts for the G20 - Díaz-Bonilla, Eugenio (Kiel Institute for the World Economy, 2018)
Achieving a “sustainable food future” (the title of one of the three priorities identify by the government of Argentina for the 2018 G20 presidency) requires building food systems that, in line with the related sustainable Development Goals (SDGs), support growth and employment, ensure social inclusiveness and equity, promote climate resilience and environmental sustainability, protect biodiversity, and generate healthy diets for all. Many policy, institutional, technological and investment innovations are needed to build such food systems. This paper focuses on the financing of the utilization of adequate technologies and innovations in agricultural production, including the ones related to soils, land, water, ecosystems, and, in general, those that have been called Climate Smart Agriculture (CSA) or Climate-friendly Sustainable Agriculture (CFSA). It explores several options to mobilize financial resources to support investments in those technologies and sustainable food systems at the scale needed to have some meaningful global impact. In particular, it argues that the creation of a project preparation and financial structuring facility of appropriate scale would help leverage scarce public-sector funds to mobilize the much larger pool of private financial funds that may be interested in participating in these investments but now lack adequately structured projects and investment vehicles to do so.